Performance of nanofiltration membrane for printing wastewater treatment - Cheah, D. W.; Ramlee, Normarina; Desa, Amira Liyana; Misdan, Nurasyikin; Hairom, Nur Hanis Hayati (Universiti Teknologi Malaysia, 2018)
Almost every manufacturing process is the major origin of wastewater with certain characteristic. Printing facility provides a wide range of waste component that is harmful to the environment and people. Those harmful waste component contains high concentration of heavy metals and dye. This paper presents one of the most promising methods to remove the heavy metals and dyes from a printing wastewater before discharging to the environment. The feasibility of commercially available NF270 membrane to treat both heavy metals and dye was thoroughly investigated. The study was carried out using a cross-flow nanofiltration membrane system at operating pressure and temperature set at 5 bar and 24 ˚C, respectively. Experimental results showed that the permeate flux of NF270 is decreased from 6.2 to 5.0 L/m2 .h after 1-h operation. Whilst, the rejection of both iron and zinc ions could be obtained up to 96.9% and 97.8%, respectively. Additionally, almost complete elimination of colour (99.6%) could be achieved using NF270 membrane. Thus, it can be concluded that the commercial NF270 membrane is promising in removing both heavy metal ions and dye from printing wastewater.